PERAMALAN ANGKA PERCERAIAN DI KABUPATEN JEMBER PADA TAHUN 2022 MENGGUNAKAN METODE ARIMA - ana safitri; Nur Salam; Aprida Siska Lestia (RAGAM: Journal of Statistics & Its Application, 2023)
Jember Regime is a locale that has the largest number of separation cases in Indonesia. Subsequently, it is important to have a measurable estimating where information from the past is utilized to foresee future prospects. The reason for this study is to break down the attributes of the information, examine the best ARIMA (Autoregressive Coordinated Moving Normal) model and conjecture utilizing the best model in Jember Regime in June - December 2022. The kind of information is quantitative with relapse estimating techniques and Box-Jenkins. Assurance of the ARIMA model is done when the information is fixed and has met the background noise prerequisites and is typically conveyed. The best demonstrating is resolved in light of huge boundaries in view of the estimation aftereffects of the Sum squared resid (SSE), Adjusted R-squared, Akaike info criterion (AIC), dan Schwarz criterion (SBC). The outcomes acquired from this study are separate from case information in Jember Rule isn't great and lopsided so doing information stationarity is vital. After the information is fixed, the best ARIMA model that meets the necessities is the ARIMA model (2,1,1). The consequences of the ARIMA (Autoregressive Coordinated Moving Normal) model (2,1,1) with the situation Zt = 0,91 Zt-1 + 0,19 Zt-2 + 0,1 Zt-3 + ?t + 0,78 ?t-1.